Evidence for genetic homogeneity in autosomal recessive generalised myotonia (Becker). Issue 11 (November 1993) - Koch, M C; Ricker, K; Otto, M; Wolf, F; Zoll, B; Lorenz, C; Steinmeyer, K; Jentsch, T J
Abstract : Generalised myotonia Becker (GM) is an autosomal recessively inherited muscle disorder. Affected subjects exhibit myotonic muscle stiffness in all skeletal muscles with marked hypertrophy in the legs. A transient muscle weakness is particularly pronounced in the arms and hands and is a typical symptom of the disorder. Recently, we showed complete linkage of the disorder GM to the gene (CLCN1) coding for the skeletal muscle chloride channel CLC-1 and the TCRB gene on chromosome 7 in German families. In the study presented here we performed linkage analysis on 14 new GM families. The GM locus was again completely linked to both the CLCN1 and the TCRB gene in all families with a combined lod score of Z = 9.26 at a recombination fraction of theta = 0.00. This confirms our previous data and supports the hypothesis that GM is a genetically homogeneous disorder. The previously detected T to G missense mutation is found on 15% of the 66 GM chromosomes counted so far.